2012
DOI: 10.1371/journal.pone.0038597
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Detecting Tumour Oxygenation Levels

Abstract: Tumours that are low in oxygen (hypoxic) tend to be more aggressive and respond less well to treatment. Knowing the spatial distribution of oxygen within a tumour could therefore play an important role in treatment planning, enabling treatment to be targeted in such a way that higher doses of radiation are given to the more radioresistant tissue. Mapping the spatial distribution of oxygen in vivo is difficult. Radioactive tracers that are sensitive to different levels of oxygen are under development and in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…However, Skeldon et al [40] showed that for vessels with very high permeability, the Robin boundary condition leads to similar results as the Dirichlet boundary condition. If this is the case of tumour capillaries with increased permeability, it could provide an advantage when solving (2), since Dirichlet boundary conditions are easier to program.…”
Section: Tissue Transport Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, Skeldon et al [40] showed that for vessels with very high permeability, the Robin boundary condition leads to similar results as the Dirichlet boundary condition. If this is the case of tumour capillaries with increased permeability, it could provide an advantage when solving (2), since Dirichlet boundary conditions are easier to program.…”
Section: Tissue Transport Modelsmentioning
confidence: 99%
“…Some models assume that the source term could be set to zero since cells do not produce oxygen [29, 3740], while others implement a different approach where the oxygen supply from the capillaries is described as a distributed source throughout the tissue with localised spikes at the vessel positions [30, 40]. …”
Section: Tissue Transport Modelsmentioning
confidence: 99%
See 3 more Smart Citations